STRUCTURE OF A PLANET SYSTEM - AS A PROBLEM IN THE MAXIMUM AND MINIMUM - Abdildin, M.M.; Abishev, M.E.; Taukenova, A.S. (Recent Contributions to Physics, 2018)
In this work sown that in the planetary system - an open system - implemented the principle of minimum collision; maximum of motion integrals and the minimum of a probe body energy.